Survivin-targeting miR-542-3p overcomes HER3 signaling-induced chemoresistance and enhances the antitumor activity of paclitaxel against HER2-overexpressing breast cancer - Lyu, Hui (Cancer Lett, 2018)
Elevated expression of HER3, which interacts with HER2 in breast cancer cells, confers chemoresistance via phosphoinositide 3-kinase (PI-3K)/Akt-dependent upregulation of Survivin. However, the underlying mechanism is not clear. Ectopic expression or specific knockdown of HER3 in HER2-overexpressing breast cancer cells did not alter Survivin mRNA levels and Survivin protein stability, supporting the notion that HER3 signaling may regulate specific miRNAs that target Survivin to alter its protein translation. Here we showed that overexpression and specific knockdown of HER3 reduced and enhanced expression of two Survivin-targeting miRNAs, miR-203 and miR-542-3p, in breast cancer cells, respectively. While the specific inhibitor of either miR-203 or miR-542-3p attenuated an anti-HER3 antibody-induced downregulation of Survivin, inhibition of miR-542-3p exhibited a better efficacy than miR-203 inhibition did. Consistently, miR-542-3p mimic was much more effective than miR-203 mimic not only in inhibition of Survivin, but also in enhancement of paclitaxel-induced apoptosis in HER2-overexpressing breast cancer cells. Moreover, the combination of miR-542-3p mimic and paclitaxel, as compared with either agent alone, significantly inhibited in vivo tumor growth of HER2-overexpressing breast cancer cells. Collectively, our data indicated that the HER3/PI-3K/Akt signaling upregulates Survivin via suppression of miR-203 and miR-542-3p. Because miR-542-3p has three binding sites on the 3′-UTR of Survivin mRNA, its mimic was able to effectively downregulate Survivin in vitro and in vivo. Thus, miR-542-3p-replacement therapy is an excellent approach to overcome HER3-mediated paclitaxel resistance and significantly enhances the antitumor activity of paclitaxel against HER2-overexpressing breast cancer.